In Pursuit of Presence or Prominence? : the Prospect of Chinese Banks' Global Expansion and Their Benchmarks /: the Prospect of Chinese Banks' Global Expansion and Their Benchmarks. (2018) - Ben, Shenglin; Yu, Jiefang; Gu, Yue; Lv, Jiamin; Zhang, Lijun; Gong, Huichao; Gu, Hanting; Shuai, Qi
No abstract available